Modulation of prelanding lower-limb muscle responses in athletes with multiple ankle sprains - Fu, S. N.; Hui-Chan, C. W. Y. (Medicine & Science in Sports & Exercise, 2007)
Purpose: The objective of this study was to investigate modulation in prelanding muscle responses and its associated impact force on landing from unexpected and self-initiated drops in male basketball players with a history of bilateral multiple ankle sprains (BMAS).